Pearl Harbor : the verdict of history - Prange, Gordon W. (Gordon William), 1910-1980.; Goldstein, Donald M.; Dillon, Katherine V. (New York : McGraw-Hill Book Co., 1986)
This book examines the underlying causes of Pearl Harbor and the revisionist theories that high officials knew of the attack. This title is the sequel to "At dawn we slept."
pt. I. The base and the summit. "We were all out there" ; "Slow in waking up" ; "Too deeply bury their hate" ; "Bait for a Japanese attack" ; "To avoid war with Japan" ; "He had supreme responsibility" ; "On lines of national policy" ; "Looking in the wrong direction" -- pt. II. Advisors, planners, and chiefs. "With knives and hatchets" ; "Unsurmountable obstacles" ; "Crimination and recrimination" ; "To help and serve" ; "Faults of omission" ; "Outside of effective contact" ; "A finger of blame" ; "Primarily a failure of men" ; "The pitfalls of divided responsibility" ; "A lack of imagination" ; "East wind rain" -- pt. III. Field commanders and operators. "A sentinel on duty" ; "Alerted to prevent sabotage" ; "The failure to comprehend" ; "An important man in an important post" ; "Peculiar, complicated and tense" ; "Always striving for perfection" ; "His most grievous failure" ; "The last critical stages" ; "It is inexplicable" -- pt. IV. The view from the crow's nest. "Blessed by the war god" ; "A strategic imbecility" ; "A mental attitude" ; "In the wake of the Pearl Harbor disaster" ; "Remember Pearl Harbor!" -- Appendix A : The Pearl Harbor investigations -- Appendix B : Japanese proposals of November 20, 1941 -- Appendix C : "War warning" messages of November 27, 1941 -- Appendix D : Proposed Modus Vivendi -- Appendix E : Japan's "bomb plot" message -- Appendix F : The hull note of November 26, 1941 -- Appendix G : Popov questionnaire.
Includes bibliographical references (pages 663-675) and index.
Keywords: Pearl Harbor (Hawaii), Attack on, 1941.